Design and Experimental Investigation of an Ultra-Low Frequency, Low-Intensity, and Multidirectional Piezoelectric Energy Harvester with Liquid as the Energy-Capture Medium - Ning Li; Fan Yang; Tao Luo; Lifeng Qin (Micromachines, 2023)
Traditional piezoelectric vibration energy harvesters (PVEHs) usually adopt a rigid energy-capture structure, which can achieve efficient energy harvesting in single-directional, high-frequency, and high-intensity vibration environments. However, efficient harvesting with the use of low-frequency, low-intensity, and multidirectional vibration energy remains a challenge for existing harvesters. To tackle this problem, we proposed a PVEH with liquid as the energy-capture medium. Our previous research verified that this set up can show a good energy harvesting performance under low-frequency, low-intensity, and horizontal multidirectional vibration excitation. In this paper, we further studied the possibility of vertical multidirectional energy harvesting using this device, as well as the influence of several important parameters (rope margin, liquid level height, and floating block shape) on the output performance. The results showed that the proposed PVEH can realize energy harvesting in three-dimensional space and that the output characteristic is adjustable.